The relationship between human coronaviruses, asthma and allergy—An unresolved dilemma - Chałubiński, Maciej (Clin Exp Allergy, 2020)
Human coronaviruses (HCoVs) such as HCoV‐229E or OC43 are responsible for mild upper airway infections, whereas highly pathogenic HCoVs, including SARS‐CoV, MERS‐CoV and SARS‐CoV‐2, often evoke acute, heavy pneumonias. They tend to induce immune responses based on interferon and host inflammatory cytokine production and promotion of T1 immune profile. Less is known about their effect on T2‐type immunity. Unlike human rhinoviruses (HRV) and Respiratory Syncytial Virus (RSV), HCoVs are not considered as a dominant risk factor of severe exacerbations of asthma, mostly T2‐type chronic inflammatory disease. The relationship between coronaviruses and T2‐type immunity, especially in asthma and allergy, is not well understood. This review aims to summarize currently available knowledge about the relationship of HCoVs, including novel SARS‐CoV‐2, with asthma and allergic inflammation.